Modest, Secure, and Informed: Successful Development in Conflict Zones - Berman, Eli; Felter, Joseph H; Shapiro, Jacob N; Troland, Erin (American Economic Review, 2013)
Most interpretations of prevalent counterinsurgency theory imply that increasing government services reduces rebel violence. Empirically, however, development programs and economic activity sometimes increase violence. Using new panel data on development spending in Iraq, we show that violence-reducing effects of development assistance are greater when: (i) projects are small; (ii) troop strength is high; and (iii) professional development expertise is available. These findings are consistent with an information-centric (“hearts and minds”) model, which implies that violence-reduction is greatest when projects are secure, valued by community members, and services derived are conditional on government control of the territory.